2021
DOI: 10.1371/journal.pgen.1009732
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening and genome-wide analyses of 44 anticancer drugs in the 1000 Genomes cell lines reveals an association of the NQO1 gene with the response of multiple anticancer drugs

Abstract: Cancer patients exhibit a broad range of inter-individual variability in response and toxicity to widely used anticancer drugs, and genetic variation is a major contributor to this variability. To identify new genes that influence the response of 44 FDA-approved anticancer drug treatments widely used to treat various types of cancer, we conducted high-throughput screening and genome-wide association mapping using 680 lymphoblastoid cell lines from the 1000 Genomes Project. The drug treatments considered in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Zero-passage organoids can test mechanisms of action by combining genetic and small-molecule perturbations. As an illustration, we pursued one gene widely implicated in resistance to anti-cancer therapies: the NAD(P)H quinone dehydrogenase 1, NQO1 [53, 54]. As part of the phase II antioxidant response, NQO1 is heterogeneously upregulated in luminal breast cancers [52, 55].…”
Section: Resultsmentioning
confidence: 99%
“…Zero-passage organoids can test mechanisms of action by combining genetic and small-molecule perturbations. As an illustration, we pursued one gene widely implicated in resistance to anti-cancer therapies: the NAD(P)H quinone dehydrogenase 1, NQO1 [53, 54]. As part of the phase II antioxidant response, NQO1 is heterogeneously upregulated in luminal breast cancers [52, 55].…”
Section: Resultsmentioning
confidence: 99%
“…The results of a high-throughput dose-response screen of 44 anticancer drugs conducted on the 1000 Genome collection of LCLs by Akhtari et al showed one significant SNP association with OXAL response, as indicated on the Manhattan plot ( Figure 1 a) [ 13 ]. This association was centered on chromosome 10, and the locus zoom plot of the region’s genes ( Figure 1 b) showed that the SNP rs11006706 ( p -value = 1.22 × 10 −9 ) exceeded genome-wide significance ( p < 10 × 10 −8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The OXAL viability data was available for all LCLs (n = 680) from a high-throughput anticancer agent screen developed by Akhtari et al [ 13 ]. Background fluorescence control, 10% dimethyl sulfoxide (DMSO), and a drug vehicle control were included on every plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro models of human gliomas have the potential to improve our understanding of glioma biology and novel therapeutic strategies [ 20 ]. High throughput drug screens utilizing cell line models have assessed the sensitivity and resistance of different compounds and identified both germline and somatic variants that influence drug response [ 21 , 22 , 23 ]. The 1000 Genomes Project collection is a valuable resource for studying the impact of diverse global human genetics on drug response and disease.…”
Section: Introductionmentioning
confidence: 99%